Upper Cretaceous carbon- and oxygen-isotope stratigraphy of hemipelagic carbonate facies from southern Tibet, China - Li, X; Jenkyns, H; Wang, C; Hu, X; Chen, X; Wev, Y; Huang, Y; Cui, J (2006)
A high-resolution carbon-isotope curve derived from Upper Cretaceous hemipelagic sediments cropping out at Tingri, southern Tibet, shows similarities to patterns established on other continents, notably in the presence of a well-defined positive excursion across the Cenomanian-Turonian boundary where δ13C values exceed 3.5‰. From the upper Turonian to the lower Campanian, δ 13C values generally decline, apart from a minor positive excursion in the middle Coniacian: a trend that departs from that recorded from Europe. Relatively low δ13C values (c. 1‰) at the Santonian-Campanian and Campanian-Maastrichtian boundaries in Tibet define a prominent broad positive excursion centred in the middle Campanian and terminated by an abrupt fall towards the close of the stage. When compared with data from Europe and North Africa, the δ13C values of the Tibetan section are generally lower by c. 1.5‰, except for the middle Campanian positive excursion where values (δ13C c. 2‰) are comparable with those documented from Europe and North Africa. These differences are interpreted as reflecting variable mixing of water masses carrying different carbon-isotope signatures, such that areas close to the major sinks of marine organic carbon recorded higher δ13C values than those located in more distal regions. Oxygen-isotope ratios, albeit affected by diagenesis, may record a palaeotemperature signal.